Pd-Catalyzed Diastereo- and Enantioselective [3+2]-Cycloaddition Reaction of Vinyl Epoxide with Nitroalkenes - Wu, Wen-Qiong; Ding, Chang-Hua; Hou, Xue-Long (Synlett, 2012)
A diastereoselective and enantioselective [3+2]-cycloaddition reaction of vinyl epoxide and nitroalkenes has been developed using Pd/1,1′-ferrocene-P,N-ligand, providing substituted tetrahydrofurans in high yields and with high diastereo- and enantioselectivities.
Keywords: vinyl epoxide; nitroalkene; palladium; asymmetric catalysis; [3+2] cycloaddition